MANFAAT PEMERIKSAAN REFRAKSI PADA ANAK SEKOLAH DASAR DI PAMULANG - Ari Haryanto; Wahyu Budiana; Bunyamin Rizki Abdillah (Jurnal Mata Optik, 2022)
This study aims to find out benefit checking refraction from an elementary school. This study uses a qualitative method, the population in this study are parents who have elementary school children in Pamulang, with a sample of 5 parents who check their children at Optik Kita Pamulang. Data collection is done by interview and documentation, interviews were conducted with 5 people interviewees. The results of this study indicate that 4 resource persons think that early refraction examination is very important to do, 1 resource person considers it normal. Only 2 resource persons examined their children based on the initiative as a preventative measure for refractive errors, the other 3 carried out examinations after experiencing symptoms.